The effect of new firm formation on regional development over time - Michael Fritsch; Pamela Mueller (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2004)
In our analysis of the impact of new firm formation on regional employment change we identified considerable time lags. We investigated the structure and extent of these time lags by applying the Almon lag model and found that new firms can have both a positive and a negative effect on regional employment. The results indicate that the indirect effects of new firm formation (crowding-out of competitors, improvement of supply conditions and improved competitiveness) are of greater magnitude than the direct effect, i.e., the jobs that are created in the new businesses. The peak of the positive impact of new firms on regional development is reached about eight years after the new firms have been started. – – Für den Einfluss von Gründungsaktivitäten auf die Regionalentwicklung lassen sich erhebliche Zeitverzögerungen feststellen. Wir analysieren das Ausmaß und die Struktur dieser Zeitverzögerungen mit dem Almon-Lag Verfahren. Die Ergebnisse zeigen, dass Gründungen sowohl einen positiven als auch einen negativen Einfluss auf das Beschäftigungsniveau haben können. Allgemein scheinen die indirekten Effekte des Gründungsgeschehens (Verdrängung etablierter Konkurrenten, Verbesserung des Angebots und gesteigerte Wettbewerbsfähigkeit) stärker ausgeprägt zu sein als der direkte Effekt, gemessen als die in den neuen Firmen entstandenen Arbeitsplätze. Das Maximum des positiven Einflusses der Gründungen auf die Regionalenwicklung wird nach ca. acht Jahren erreicht.
Keywords: M13; O1; O18; R11; 330; Regional growth; new firms; entrepreneurship; time lags; Regionalentwicklung; Unternehmensgründungen; Entrepreneurship; Time Lags; Unternehmensgründung; Entrepreneurship-Ansatz; Regionale Entwicklung; Lag-Modell; Schätzung; Deutschland